2015
DOI: 10.1038/onc.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

The TEL-AML1 fusion protein of acute lymphoblastic leukemia modulates IRF3 activity during early B-cell differentiation

Abstract: The t(12;21) translocation is the most common genetic rearrangement in childhood acute lymphoblastic leukemia (ALL) and gives rise to the TEL-AML1 fusion gene. Many studies on TEL-AML1 describe specific properties of the fusion protein, but a thorough understanding of its function is lacking. We exploited a pluripotent hematopoietic stem/progenitor cell line, EML1, and generated a cell line (EML-TA) stably expressing the TEL-AML1 fusion protein. EML1 cells differentiate to mature B-cells following treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Upon TEL-AML1 expression, EML1 cells lost the capacity to differentiate into B-cells and underwent apoptosis. TEL-AML1 expression impaired the activation of IFNa/b signalling pathway in primary murine and human HSPCs with a dramatic inhibition of IRF3 phosphorylation, a member of the IFN-regulatory transcription factor family (de Laurentiis et al, 2015). This finding is consistent with the downregulation of genes involved in IRF3-IFN signalling as shown in gene expression data derived from blasts of ALL patients expressing TEL-AML1 (Linka et al, 2013).…”
Section: Biological Plausibilitysupporting
confidence: 78%
See 1 more Smart Citation
“…Upon TEL-AML1 expression, EML1 cells lost the capacity to differentiate into B-cells and underwent apoptosis. TEL-AML1 expression impaired the activation of IFNa/b signalling pathway in primary murine and human HSPCs with a dramatic inhibition of IRF3 phosphorylation, a member of the IFN-regulatory transcription factor family (de Laurentiis et al, 2015). This finding is consistent with the downregulation of genes involved in IRF3-IFN signalling as shown in gene expression data derived from blasts of ALL patients expressing TEL-AML1 (Linka et al, 2013).…”
Section: Biological Plausibilitysupporting
confidence: 78%
“…De Laurentiis et al (2015) generated an experimental model using the murine haematopoietic stem progenitor cell line EML1 expressing the TEL-AML1 fusion protein, and analysed its differentiation and global gene expression properties. Upon TEL-AML1 expression, EML1 cells lost the capacity to differentiate into B-cells and underwent apoptosis.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…5C, upper). We induced B cell differentiation by coculturing the EML cells with OP9 stromal cells in the presence of IL-7 and Flt3L for 6 d [42,43]. After 6 d of coculture, stably transduced EML cultures contained ;4.2 million B220 + B cells, whereas MSCV-mirn23a-transduced EML cells contained ,400,000 B220 + B cells ( Fig.…”
Section: Increased B Lymphopoiesis Of Mirn23a 2/2 Progenitors During mentioning
confidence: 99%
“…As a transcriptional repressor, the TEL (also called ETV6 ) gene at human chromosome 12p13 encodes a member of the ETS family of transcription [5]. The TEL protein, which belongs to a subset of ETS proteins, regulates the development and growth of diverse cell types, particularly those of hematological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic manipulation studies in mice indicated that this gene is required for the development and maintenance of bone marrow-based blood cell formation and the vascular network [7]. However, the TEL gene frequently suffers various mutations that leads to an array of potentially lethal cancers, such as hematological malignancies, usually as a result of its fusion with many partner genes, such as 21q22 (TEL-AML1), 5q33 (TEL-PDGFRβ), 9q34 (TEL-ABL), 9p24 (TEL-JAK2), and 3q26 (TEL-EVI1) [5, 8-11]. It has been reported that the TEL gene is the target of the translocation t(12; 22)(p13;q12), which is a recurrent but infrequent chromosome abnormality in human myeloid malignancies [12].…”
Section: Introductionmentioning
confidence: 99%